Compact piezoelectric micromotor with a single bulk lead zirconate titanate stator - Yan, Liang (2013)
The advance of micro/nanotechnology promotes the development of micromotors in recent years. In this article, a compact piezoelectric ultrasonic micromotor with a single bulk lead zirconate titanate stator is proposed. A traveling wave is generated by superposition of bending modes with 90 phase difference excited by d15 inverse piezoelectric effects. The operating principle simplifies the system structure significantly, and provides a miniaturization solution. A research prototype with the size of 0.75x0.75x1.55mm is developed. It can produce start-up torque of 0.27uNmand maximum speed of 2760 r/min at 14RMS.